To simplify the given expression we need to remove the radical from the denominator by rationalizing it.
To rationalize a radical expression first step is multiply both numerator and denominator of the expression by the conjugate of it's denominator.
So, conjugate of 6+√3 = 6-√3.
Hence,
![(1)/(6+√(3)) *(6-√(3))/(6-√(3))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tlml7qez0f57ofv4bgxdkxj8wtatqluzro.png)
=
=
Since (a+b)(a-b)= a^2-b^2
=
![(6-√(3))/(36-3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/razcps5ivxahvwc92mw6lovdhoj7zrfj3b.png)
=
![(6-√(3))/(33)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kbbcozq7tg917zwzcgmkski9vgg3dz5p0t.png)
So, the answer is
![(6-√(3))/(33)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kbbcozq7tg917zwzcgmkski9vgg3dz5p0t.png)